Analisis Nilai Sosial pada Novel “Barata Yudha” karya Sunardi D.M dalam Perspektif Islam - Ridwan, Fachrur Rajabani (El-Ghiroh : Jurnal Studi Keislaman, 2021)
This study aims to determine the social values ​​contained in the novel "Barata Yudha" by Sunardi D.M. Then studied using qualitative methods in an Islamic perspective. The object of the objective is clear in the novel "Barata Yudha" itself, and the main sources of the Islamic perspective used are the Qur'an and hadith. The research technique used is reading the whole novel, looking for data in the form of social values ​​in it, collecting data, studying it with an Islamic perspective sourced from the Qur'an and hadith, and drawing conclusions. It turns out that Islam is indeed a perfect religious teaching, this is evidenced by the various rules in it which include social values ​​from novels with historical backgrounds of other religions.